Chiral Soliton Models for Baryons - Weigel, Herbert; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
This concise research monograph introduces and reviews the concept of chiral soliton models for baryons. In these models, baryons emerge as (topological) defects of the chiral field. The many applications shed light on a number of bayron properties, ranging from static properties via nucleon resonances and deep inelastic scattering to even heavy ion collisions. As far as possible, the theoretical investigations are confronted with experiment. Conceived to bridge the gap between advanced graduate textbooks and the research literature, this volume also features a number of appendices to help nonspecialist readers to follow in more detail some of the calculations in the main text.
and Motivation -- Quark Flavor Interaction -- Self-consistent Soliton -- The Skyrme Model -- Soliton Quantization in Flavor SU(2) -- Soliton Quantization in Flavor SU(3) -- Baryon Properties -- Meson–Baryon Scattering in Chiral Soliton Models -- Exotic Baryons -- Multi-baryon Systems in the Skyrme Model.
Keywords: Nuclear physics; Heavy ions; Elementary particles (Physics).; Quantum field theory; Particle and Nuclear Physics; Nuclear Physics, Heavy Ions, Hadrons; Elementary Particles, Quantum Field Theory